Type 1 Interferon Gene Signature Promotes RBC Alloimmunization in a Lupus Mouse Model - Lee, June Young; Madany, Emaan; El Kadi, Najwa; Pandya, Sumaarg; Ng, Kessandra; Yamashita, Michifumi; Jefferies, Caroline A.; Gibb, David R. (Frontiers in Immunology, 2020)
Red blood cell (RBC) transfusion exposes recipients to hundreds of unmatched minor RBC antigens. This exposure can lead to production of alloantibodies that promote clinically significant hemolytic events. Multiple studies have reported an increased frequency of RBC alloimmunization in patients with autoimmunity. However, cellular and molecular mechanisms that underlie autoimmunity-induced alloimmunization have not been reported. Patients with systemic lupus erythematosus (SLE) have a high frequency of alloimmunization and express a type 1 interferon (IFNα/β) gene signature. Thus, we utilized the pristane-induced lupus mouse model to test the hypothesis that inflammation in lupus promotes RBC alloimmunization, and to examine the potential role of IFNα/β. Intraperitoneal injection of pristane, a hydrocarbon oil, led to autoantibody production, glomerulonephritis, and pulmonary hemorrhage in wildtype (WT) mice. Pristane treatment significantly induced serum IFNα and expression of multiple interferon-stimulated genes (ISGs) in peripheral blood and peritoneal fluid cells, including inflammatory macrophages. Following transfusion with allogeneic RBCs expressing the KEL glycoprotein, pristane-treated WT mice produced significantly elevated levels of anti-KEL IgM and anti-KEL IgG, compared to untreated mice. Pristane induced comparable levels of inflammatory cells and cytokines in mice lacking the IFNα/β receptor (IFNAR1-/-) or the IFNα/β-inducing transcriptions factors (IRF3/7-/-), compared to WT mice. However, pristane-treated IFNAR1−/− and IRF3/7−/− mice failed to produce ISGs and produced significantly lower levels of transfusion-induced anti-KEL IgG, compared to WT mice. Thus, pristane induction of a lupus-like phenotype promoted alloimmunization to the KEL RBC antigen in an IFNα/β-dependent manner. To our knowledge, this is the first examination of molecular mechanisms contributing to RBC alloimmunization in a model of autoimmunity. These results warrant further investigation of the role of IFNα/β in alloimmunization to other RBC antigens and the contribution of the IFNα/β gene signature to the elevated frequency of alloimmunization in patients with SLE.